2017
DOI: 10.31254/jmr.2017.3304
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Presentation of Down’s syndrome: A case report

Abstract: Down's Syndrome or Trisomy 21 is the most common chromosomal abnormality occurring in human leading to mental retardation and stunted growth. It is considered as a genetic disorder with a defect in all or a part of a third copy of chromosome 21. This article highlights varied clinical presentation of 18 year old patient with Down's Syndrome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 4 publications
0
4
0
Order By: Relevance
“…Development of DS brain is associated with reduction in the neuronal number and abnormal neuronal differentiation. It has been previously reported that DS neuron degenerate subsequently and undergoes apoptosis [4]. The mental retardation with full trisomy 21 is found in almost all patients, and it is basically oligophrenia at the stage of imbecility (65-90%).…”
Section: Reviewmentioning
confidence: 96%
See 2 more Smart Citations
“…Development of DS brain is associated with reduction in the neuronal number and abnormal neuronal differentiation. It has been previously reported that DS neuron degenerate subsequently and undergoes apoptosis [4]. The mental retardation with full trisomy 21 is found in almost all patients, and it is basically oligophrenia at the stage of imbecility (65-90%).…”
Section: Reviewmentioning
confidence: 96%
“…When screening by nuchal translucency (NT), about 83% of trisomy 21 pregnancies were identified in the first trimester. Later, it was revealed that screening by a combination of maternal age, NT and bitest (PAPP-A with second trimester β-hCG) or tri-test [alpha-fetoprotein (AFP), estriol and free β-hCG] has a potential sensitivity of 94% for a 5% false positive rate [4,33]. However, Ruei-Yu Lan et al, reported about multicenter study of 29,137 cases that enrolled the chromosomal abnormality screening from Taipei city.…”
Section: Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…The tonsils and adenoids also grown in size. Dental anomalies among DS individuals are frequently associated with tooth morphology, such as a decreased root to crown ratio, decreased tooth size, hypodontia or partial anodontia, and delayed eruption (Mathew et al, 2017;Rai et al, 2022).…”
Section: Introductionmentioning
confidence: 99%